THERAPEUTIC EFFECTS OF LOW-LEVEL LASER AND REFLEXOLOGY ON ADHESIVE CAPSULITIS IN ELDERLY TYPE 2 DIABETIC PATIENTS - Soliman, Ayman S; Mahmoud, Ayman M; Serry, Zahra; Dawood, Fady (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â  Â Objective: Adhesive capsulitis is common in Type 2 diabetic patients. The painful nature of adhesive capsulitis and the lack of effective therapy for improving motion and diminishing pain demonstrate the demand for a new effective therapeutic intervention. The current study aimed to determine the efficacies of low-level laser therapy (LLLT) and reflexology for improving range of motion (ROM) in diabetic patients with adhesive capsulitis. Methods: Forty volunteer patients of both sexes with proven Type 2 diabetes and adhesive capsulitis were included in the current study. The patients were divided into two groups each comprising 20 patients as follows; Group I (LLLT): Patients received LLLT for 15 minutes and Group II (Reflexology): Patients received reflexology in the form of thumb walk for 15 minutes. Therapy was applied 3 times/week for 8 weeks with concurrent 15 minutes exercise. Results: Patients received LLLT showed a significant increase in ROM of abduction, internal rotation, flexion, and external rotation at the end of 4 and 8 weeks. Reflexology induced a significant improvement in shoulder ROM at 8 weeks posttreatment, however, its effect on internal rotation ROM was non-significant at the end of 4 weeks period. Conclusion: LLLT and reflexology significantly improved ROM and reduced pain severity in diabetic patients with adhesive capsulitis; LLLT seemed to be more effective. Thus, both therapies may be recommended in the treatment of frozen shoulder, pending further investigations to trace out their exact efficacies. Keywords: Adhesive capsulitis, Diabetes complications, Laser, Reflexology.